PERAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KORBAN BENCANA ALAM GUNUNG SINABUNG DI MTsN NEGERI KARO KABUPATEN KARO - Khairuddin Tambusai; Wulan Rama (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
The background of this study is to find out the role of BK teachers in increasing the motivation to learn students of natural disaster victims in MTsN Karo District. Karo, this was known through observation of interviews with BK teachers. Students who are victims of natural disasters appear to be anxious at the time of eruption of a mountain, causing the student to not focus during the learning process. Information services can be implemented by BK teachers in helping to increase the motivation to learn students ofnatural disaster victims. Peran Guru Bimbingan Konseling Dalam Meningkatkan Motivasi Belajar Siswa Korban Bencana Alam Gunung Sinabung Di Mtsn Negeri Karo Kabupaten Karo This research aims to find out how the role of BK teachers in improving student motivation to learn victims of natural disasters in MTsN Karo District. Karo This study uses qualitative research with a descriptive research approach that produces adescription in the form of written or oral words from the behavior of the participants and also research subjects that can be observed from social situations. After doing the research, it was found that the role of the BK teacher in increasing the motivation to learn students of natural disaster victims in MTsN Karo District. Karo, showed a pretty good change, where BK teachers provide services according to students' needs or according to what problems students are facing.Keywords: The Role of BK Teachers, Student Learning Motivation of Mount Sinabung